Synthesis and Anticancer Activity of Some New Derivatives of Coumarin and Quinolinyl Mercaptotriazoles - Mona A. Hosny; Hyam A. Radwan; Emtithal A. El-Sawi (E-Journal of Chemistry)
Pechmann condensation of ethylacetoacetate with derivatives of phenol by heating in absence of solvent and with montmorillonite clays K-10 afforded coumarin derivatives (1a-e) in good yields which on reaction with thiosemicarbazide in anhydrous pyridine yielded coumarin-quinolinyl mercaptotriazole (2a-e). The latter compounds were evaluated for their antimicrobial and anticancer activities. The newly synthesized compounds were characterized by IR, 1HNMR and mass spectra.